Integrating MATLAB in teaching linear programming at the university level - Erna Puji Astutik; Sri Rahmawati Fitriatien (International Journal on Teaching and Learning Mathematics, 2018)
Learning in higher education is inseparable from the role of lecturers in preparing learning, one of which is by preparing learning media that can help and guide students in understanding the material. One of the software that can be developed as a media in mathematics learning is MATLAB. This descriptive research used the integration of MATLAB in teaching and learning linear programming. The subject of this research were students in mathematics education class 2016B Universitas PGRI Adi Buana Surabaya. Data were collected by observation and questionnaire. From the data, can be concluded that by utilizing MATLAB on Linear Programming, students were able to use the MATLAB in understanding and solving Linear Programming problems. Students also gave positive responses toward the integration of MATLAB in linear programming teaching and learning.